Riwayat Gangguan Jiwa pada Keluarga dengan Kekambuhan Pasien Skizofrenia di RSUP Dr Sardjito Yogyakarta - Ratna Dewi, Carla R Marchira (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Schizophrenia is severe mental disorder with the highest proportion and relapse in Sardjito Hospital inpatient section. Report on relapse incident of schizophrenia is 60%-75%. Family histories of mental disorder are reported as risk factors of relapse in schizophrenic patients.Objective: To identify relationship between family histories of mental disorder and relapse in schizophrenic patient in Sardjito Hospital Yogyakarta.Method: Subjects were  schizophrenic patient who were hospitalized in Sardjito Hospital Yogyakarta between May 2007 - May 2008. The figure of sample was 47 people. Data was collected using structured questionnaire on demography and  family histories of mental disorder. This is cross sectional and descriptive analytic study. Data was analyzed using univariate analysis and multivariate analysis stepwise logistic regression.Result:  Data collection showed that mean of subject’s age is 34 years. Number of males and females is equal and most of the subject is unemployee and unmarried. Majority of subject came from low socioeconomic. Educational background of subject is mostly high school. Out of 47 samples relapse rate is 55,3%. As much as 24 samples (51,1%) have family histories of mental disorder. There were 68,1% patients showed uncompliance in medication. This study showed 3 variables which have relationship with relapse in schizophrenic patient; those were age (p=0,036), family histories of mental disorder (p=0,029) and drug compliance (p=0,007).Conclusion:  There is relationship betweeen family history of mental disorder and relapse in schizophrenic patient in Sardjito Hospital Yogyakarta. Multivariate analysis showed that drug compliance is the most significant influencing relapse in schizophrenic patients.Keywords: family histories of mental disorder, drug compliance, schizophrenia, relapse